PENGARUH MOTIVASI KERJA TERHADAP PENINGKATAN KINERJA KARYAWAN - Prilanitasari Prilanitasari; Noer Mutiara Ningsih, Suci Adelia Salma, Sulistiasih (CV. Adiba Aisha Amira, 2024)
Motivation is what causes, channels and supports human behavior so that we can work diligently and enthusiastically to optimum results. Extrinsic motivation as part of the work motivation itself is also believed to have a positive and significant influence on employee performance.Stefan Ivanko (2012; 70) defines motivation as the desire and energy of a person directed towards achieving a goal. Motivation is the cause of action.To try to influence someone in order to give motivation means to get and then want to do what is known and what is done. Motivation can be intrinsic and extrinsic.Performance is the quality and quantity of work achieved by an employee in carrying out his or her duties in accordance with the responsibilities assigned to him or her. (Mangkunegara, 2004:67). The success of a company anywhere and moving in any field depends fundamentally on the success of management in carrying out its work. The degree of success of a company can be seen from the performance of the company in managing its human resources. It requires the company to be able to have quality human resources, because these resources are invaluable assets for the company. The achievement of the objectives of the company does not depend only on modern equipment, facilities and complete equipment, but rather more on the man who carries out the work.